Can a successional crop system associated with preemergent herbicides be a tool to control weeds? - Rampazzo, Pedro Eduardo; Alves, Tavvs Micael; Jakelaitis, Adriano; Tejada, Jorge Luis [UNESP] (Instituto Biológico, 2022)
The objective of this research was to evaluate weed control in a successional soybean-sorghum system by using preemergent herbicides. Two trials were conducted in soybean and two in sorghum, in different soil types (sandy in Rio Verde city and clayey in Montividiu city). All trials were established in a completely randomized block design with five preemergent herbicides in soybean (rates in): diclosulam 35.3 g a.i.·ha–1, chlorimuron 20 g a.i.·ha–1, sulfentrazone 200 g a.i.·ha–1, flumioxazin 50 g a.i.·ha–1, S-metolachlor 1728 g a.i.·ha–1, and two controls (hand weeded and untreated). Treatments in sorghum trials were the same to the soybean plus atrazine 1250 g a.i.·ha–1 and atrazine 1250 g a.i.·ha–1 + S-metolachlor 1728 g a.i.·ha–1. All treatments had four replicates. Weed control was assessed at 7, 14, 21 and 28 days after planting (DAP) in both crops. In addition, yield was measured when grains reached physiological maturity. All preemergent herbicide treatments successfully controlled weeds, specially Commelina benghalensis, Cenchrus echinatus and Eleusine indica, in both soybean trials until 28 DAP. In some weeds of sorghum, sulfentrazone, diclosulam and chlorimuron sprayed at soybean preemergence performed better than atrazine sprayed at sorghum preemergence. All preemergent herbicides sprayed at soybean preemergence did not affect soybean and sorghum yield, showing similarity with the hand weeded treatment. The results of this research provide evidence that the mix of crop succession and preemergent herbicide applications can be a strong strategy for integrated weed management.
Keywords: weed management; residual herbicides; Glycine max; Sorghum bicolor